Phosphorylation and IGF-1-mediated dephosphorylation pathways control the activity and the pharmacological properties of skeletal muscle chloride channels - De Luca, Annamaria (1998)
1. In the present study we tested the hypothesis that insulin-like growth factor-1 (IGF-1) modulates resting chloride conductance (G(Cl)) of rat skeletal muscle by activating a phosphatase and that the chloride channel, based on the activity of phosphorylating-dephosphorylating pathways, has different sensitivity to specific ligands, such as the enantiomers of 2-(p-chlorophenoxy) propionic acid (CPP). 2. For this purpose G(Cl) in EDL muscle isolated from adult rat was first lowered by treatment with 5 nM 4-β-phorbol 12,13 dibutyrate (4-β-PDB), presumably activating protein kinase C (PKC). The effects of IGF-1 and of the enantiomers of CPP on G(Cl) were then tested. 3. IGF-1 (3.3 nM) had no effect of G(Cl) on EDL muscle fibres in normal physiological solution, whereas it completely counteracted the 30% decrease of G(Cl) induced by 4-β-PDB. No effects of IGF-1 were observed on G(Cl) lowered by the phosphatase inhibitor okadaic acid (0.25 μM). 4. Ceramide, reported to activate on okadaic acid-sensitive phosphatase, mimicked the effects of IGF-1. In fact, N-acetyl-sphingosine (2.5–5 μM), not very effective in control conditions, increased the G(Cl) lowered by the phorbol ester, but not the G(Cl) lowered by okadaic acid. 5. In the presence of 4-β-PDB, G(Cl) was differently affected by the enantiomers of CPP. The S(−)-CPP was remarkably less potent in producing the concentration-dependent reduction of G(Cl), whereas the R(+)-CPP caused an increase of G(Cl) at all the concentrations tested. 6. In conclusion, the PKC-induced lowering of G(Cl) is counteracted by IGF-1 through an okadaic acid sensitive phosphatase, and this effect can have therapeutic relevance in situations characterized by excessive channel phosphorylation. In turn the phosphorylation state of the channel can modulate the effects and the therapeutic potential of direct channel ligands.